2016
DOI: 10.14260/jemds/2016/679
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Acute Pelvic Pain

Abstract: BACKGROUNDAcute pelvic pain can result from the gastrointestinal, gynaecological and/or urological systems. Ultrasound can be used as an initial imaging modality in the evaluation of acute pelvic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Upon data analysis, the most common sonographic findings causing pelvic pain were intramural uterine fibroids (12%), and hemorrhagic ovarian cysts (10%). This is correlated with the study conducted by Kamlesh Gupta et al in 2015 which showed that in adnexal pathologies causing pelvic pain hemorrhagic ovarian cysts are more common comprising 50 % pathologies of acute pelvic pain 9 . This is also correlated well with the past study conducted in 2002 which showed that hemorrhagic ovarian cyst and salpingitis are more commonly diagnosed adnexal pathologies in patients with pelvic pain [8] .…”
Section: Discussionsupporting
confidence: 88%
“…Upon data analysis, the most common sonographic findings causing pelvic pain were intramural uterine fibroids (12%), and hemorrhagic ovarian cysts (10%). This is correlated with the study conducted by Kamlesh Gupta et al in 2015 which showed that in adnexal pathologies causing pelvic pain hemorrhagic ovarian cysts are more common comprising 50 % pathologies of acute pelvic pain 9 . This is also correlated well with the past study conducted in 2002 which showed that hemorrhagic ovarian cyst and salpingitis are more commonly diagnosed adnexal pathologies in patients with pelvic pain [8] .…”
Section: Discussionsupporting
confidence: 88%
“…Ultrasound is the most often used imaging modality for evaluating PID. Healthy women can have fluid both in the endometrium and the cul-de-sac, but individuals with pelvic inflammatory illness may have little or no free fluid ( 14 ) , as illustrated in Fig. 2 .…”
Section: Discussionmentioning
confidence: 99%